Multicentric Post-marketing Surveillance (PMS) Observational Study of Ascorbic Acid and Zinc Effervescent Tablets in Indian Patients with Vitamin C and Zinc Deficiency - Swami, Ruchika; Sunena (Reviews on Recent Clinical Trials, 2025)
AimThe objective of this Multicentric Post-Marketing Surveillance (PMS) study was to evaluate the safety and tolerance of vitamin C and zinc tablets in the Indian population experiencing deficiencies of these nutrients. Furthermore, the study aimed to provide insights into physicians' prescription practices and characterise the patient population receiving the study medication.MethodsThis prospective observational study involved 358 participants from 8 study sites across India (including 2 government hospital sites), spanning a duration of approximately 12 weeks (3 months). The primary aim was to evaluate the safety and tolerability of zinc and ascorbic acid effervescent tablets for those who were deficient in zinc and vitamin C. Throughout the study period, adverse events were monitored and categorised by MedDRA Primary System Organ Class and Preferred Term. The analysis included evaluating the incidence, percentage, and correlation of adverse events with the treatment (safety population). Additionally, the frequencies of adverse drug reactions were examined across all enrolled patients. Vital signs and symptom-focused physical examinations were conducted during each visit in the safety population.ResultsOut of 358 (100%) patients, only 12 (3.35%) experienced minor symptoms in the study period. The majority of patients reported gastrointestinal disorders, i.e., two (0.6%) patients reported constipation and gastritis, respectively. Diarrhoea was reported by four (1.1%) patients. One (0.3%) patient reported gastrointestinal pain. Three (0.8%) patients reported vomiting. Diarrhoea was the most common symptom reported. All patients possess a mild intensity of adverse drug reactions in safety populations. The p-value is less than 0.05 (p-value < 0.05), and therefore there is a statistically significant relationship between the predictor variables and the response variable (i.e., the expected count of adverse drug reactions).ConclusionThe fixed-dose combination of vitamin C and zinc effervescent tablets appears to be safe and tolerable for the treatment of vitamin C and zinc deficiencies in Indian patients. The favorable outcome underscores the mild nature of the adverse reactions and the right medical interventions and support.
Keywords: Ascorbic acid